Pengaruh Economic Value Added Terhadap Kinerja Perusahaan Manufaktur Sektor Food and Beverage Yang Terdaftar di BEI - Lestari, Henny Setyo; Hartini; Alfad Alfarizki (Ekonomi Digital, 2025)
This study aims to determine the economic value added, refined economic value added, economic value added momentum and control variables, namely current ratio, debt to equity ratio and total assets turnover have a significant effect on company performance as measured by return on assets (ROA) of the Food and Beverage Manufacturing Sector listed on the IDX. This study uses the Panel method. The data used during the period 2018-2022 were obtained from the IDX. The dependent variable used in this study is profitability with the measurement variable being return on assets. While the independent variables are EVA, REVA and EVA momentum and the control variables are current ratio, debt equity ratio and total asset turnover. It is expected that the results of the study show that EVA, REVA and EVA have a positive and significant effect on influencing the profitability of manufacturing companies in the Food and Beverage sector in Indonesia.